Analisis dan Perancangan Sistem Informasi Kepegawaian Berbasis Website Berdasarkan Model FAST pada Kantor UPTD DPPKAD Pangkal Pinang - Hengki, Hengki; Novitasari, Ayu (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2017)
Personnel information system is one of important operational activities at UPTD office DPPKAD Pangkalpinang. However, the current operational activities are still handled with a manual system. This results in frequent disintegration of data resulting in less effective and efficient, especially in terms of time and energy. This study aims to design a website-based personnel information system required UPTD DPPKAD so as to improve the performance of UPTD DPPKAD Pangkalpinang employees in collecting data employees. In analyzing and designing the application of personnel information system, the writer uses the FAST research model which consists of six phases: initial investigation, problem analysis, needs analysis, decision analysis, system design, and system construction. For research method writer use object-oriented method, and tools use UML (Unified Modeling Language). This system is expected to accelerate and facilitate TU staff in collecting and looking for employee data. Personnel information system UPTD DPPKAD-based website can be used easily, user friendly and can be done flexibly.Keywords-Employee Information System, FAST Model, and UPTD DPPKAD Pangkalpinang.